2015
DOI: 10.1007/s11136-015-1019-2
|View full text |Cite
|
Sign up to set email alerts
|

Subjective perceptions of cognitive deficits and their influences on quality of life among patients with schizophrenia

Abstract: Patients' perceptions of their social cognitive function (but not neurocognitive functioning) have a significant impact on their QoL. Clinicians' ratings of patients' cognitive deficits were only weakly correlated with patients' subjective perceptions of their own neurocognitive, suggesting a mismatch between clinician and patient assessments of such deficits. Closer attention should therefore be paid toward patients' perception of their own deficits by clinicians in order to improve QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 53 publications
1
10
0
2
Order By: Relevance
“…Though some view this association between subjective cognitive measures and depression as a limitation, others posit that this association is clinically useful as an indication of patients’ distress (Saffer et al, 2015; Lai et al, 2014). Moreover, Caqueo-Urízar et al (2015) found that subjective cognition correlated more strongly than objective cognition with quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Though some view this association between subjective cognitive measures and depression as a limitation, others posit that this association is clinically useful as an indication of patients’ distress (Saffer et al, 2015; Lai et al, 2014). Moreover, Caqueo-Urízar et al (2015) found that subjective cognition correlated more strongly than objective cognition with quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Parece que la percepción de los usuarios de su propia cognición social tendría un impacto significativo en la evaluación de su calidad de vida 9,10 .…”
Section: Discussionunclassified
“…Durante los últimos años, una parte importante de la investigación sobre esquizofrenia y otros trastornos psicóticos se ha centrado en conocer los déficits en diversos componentes y procesos de la cognición social, entre ellos las habilidades empáticas, así como la influencia y la relación de estas alteraciones con otras variables como la sintomatología clínica, el rendimiento neurocognitivo y el funcionamiento social [6][7][8] . Sin embargo, los estudios que analizan la relación entre la cognición social en general (en particular la empatía) y la calidad de vida en personas con diagnóstico en esquizofrenia son muy escasos 9,10 . Asimismo, apenas existen estudios sobre el estado de los diversos componentes de la cognición social y de la empatía en usuarios con trastornos psicó-ticos en tratamiento en programas de rehabilitación psicosocial 11 .…”
unclassified
“…This finding is in agreement with previous reports that patients’ perception of cognitive impairments has a significant negative impact on quality of life. 44 …”
Section: Discussionmentioning
confidence: 99%